Sweden : 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report ;, 2009)
This 2009 Article IV Consultation highlights that Sweden has been hit hard by the global financial crisis. Two of its banks built up large exposures in the Baltics that significantly increased loan losses beyond normal recessionary levels. In response to the crisis, the authorities have taken wide-ranging measures to stabilize the financial system and support demand. Executive Directors have welcomed the authorities' prompt and appropriate policy responses, which have allayed immediate concerns with financial sector stability, and have helped cushion domestic demand.